Innovative Methods of Teaching. (Journal of Oriental Studies, 2016)
Basically teaching must include two major components sending and receiving information. Ultimately, a teacher tries his best to impart knowledge as the way he understood it. The use of innovative methods in educational institutions has the potential not only to improve education, but also to empower people, strengthen governance and galvanize the effort to achieve the human development goal for the country. The purpose of this paper is to suggest useful innovative teaching methods that can be attempted in imparting knowledge to the students.
Keywords: innovation; technique; teaching; and educational institutions